Demand Analysis of a Psychiatric Emergency Room and an Adolescent Acute Inpatient Unit in the Context of the COVID-19 Pandemic in Madrid, Spain - Díaz de Neira, Mónica; Blasco-Fontecilla, Hilario; García Murillo, Lourdes; Pérez-Balaguer, Ana; Mallol, Leticia; Forti, Azul; Del Sol, Pablo; Palanca, Inmaculada (Frontiers in Psychiatry, 2021)
Introduction: COVID-19 represents a serious threat to mental health worldwide. The aim of this study is to identify changes in adolescent psychiatry treatment demand in a tertiary hospital in Madrid during the first month (11th March to 11th April) after the Pandemic declaration by the OMS. We hypothesized that fear of contagion within COVID-19 may deter people to asking for psychiatric care. Method: The current study is retrospective, observational, and transversal. We reviewed the clinical records of 89 adolescents attending the Emergency Room (ER) or hospitalized at the Acute Inpatient Unit (AIU) at the Puerta de Hierro University Hospital-Majadahonda (PHUH-M) between March 11th and April 11th. Socio-demographic, clinical and demand variables were included in the study. Chi-square or Fisher exact tests were performed to compare categorical variables. We used the U Mann-Whitney test to compare quantitative variables. The level of statistical significance was set at p< 0.05. Analyses were conducted using SPSS v11.0. Results: The number of adolescents demanding psychiatric care at the ER dropped from 64 adolescents in 2019 to 25 in 2020. Similarly, the psychiatric demand collapsed from 31 to 18 patients when comparing 2019 and 2020. Furthermore, there was a trend for a decrease in the average hospital stay in 2020 when compared to 2019 (8.94 ± 4.87 vs 14.32 ±10.23, p=0.08). Self-injurious thoughts and behaviors were the most predominant reasons for consultation at both ER and AIU. Conclusion: The demand for adolescent psychiatric care decreased in the first month after the declaration of the pandemic. Our findings may be explained by: 1) the fear of contagion; 2) the strict confinement measures; and 3) the initial shock as an adaptive reaction described in other disasters. Further studies are needed.